2011
DOI: 10.1177/1086296x11413720
|View full text |Cite
|
Sign up to set email alerts
|

Activists, Allies, and Racists

Abstract: Teachers often resist discussions about racism in the classroom, yet it is a topic that is frequently addressed in multicultural literature. This study examines teachers in a graduate reading program (N = 58) who used picture books reflecting African American heritage with elementary school children in a summer reading practicum. Prior to teaching children, a subset of these teachers participated in a course that addressed issues of racism, allowing for an investigation of a course effect on teachers' comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Addressing this work in our classrooms is an especially important task because prior research has revealed that teachers' implicit biases negatively affect instruction (Hollingworth, 2009;Mason, 2017). Students as young as preschool exhibit racial bias and a preference for whites (Baron & Banaji, 2006;Jordan & Hernandez-Reif, 2009;Shutts, 2015;Zinser, Rich, & Bailey, 1981), yet attitudes toward race evolve when students are engaged in racial literacy lessons (Lazar & Offenberg, 2011). Therefore, addressing racial illiteracy through literacy instruction is critical (Boutte, Lopez-Robertson, & Powers-Costello, 2011;Priest et al, 2016;Roy, 2017).…”
Section: Racial Illiteracymentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing this work in our classrooms is an especially important task because prior research has revealed that teachers' implicit biases negatively affect instruction (Hollingworth, 2009;Mason, 2017). Students as young as preschool exhibit racial bias and a preference for whites (Baron & Banaji, 2006;Jordan & Hernandez-Reif, 2009;Shutts, 2015;Zinser, Rich, & Bailey, 1981), yet attitudes toward race evolve when students are engaged in racial literacy lessons (Lazar & Offenberg, 2011). Therefore, addressing racial illiteracy through literacy instruction is critical (Boutte, Lopez-Robertson, & Powers-Costello, 2011;Priest et al, 2016;Roy, 2017).…”
Section: Racial Illiteracymentioning
confidence: 99%
“…At first, primary grades may seem inappropriate for anti-racism discussions and social justice awareness work, but young students often have an innate sense of fairness that enhances many developmentally appropriate resources. The richness of multicultural literature provides excellent fodder for conversations to improve racial literacy and deepen students' awareness of activism and inequity (Lazar & Offenberg, 2011). Collaboratively reading The Name Jar by Yangsook Choi allowed our students to tell personal stories about their names, giving respect to the uniqueness of each name across the many cultures represented in our class.…”
Section: Using Picture Books To Promote Conversationmentioning
confidence: 99%
“…Complementing these essays, JLR put forward compelling research that investigated instructional approaches to affirming ethnic or cultural diversity along with ending racial inequities within literacy pedagogy and curriculum (e.g., Ajayi, 2015; Dutro, 2002; Egan-Robertson, 1998; Fairbanks, 1998; Guthrie, Coddington, & Wigfield, 2009; Ives, 2011; Lazar & Offenberg, 2011; Maloch, 2005; May, 2011; Perry, 2008; Rex, 2006). These studies explored readers’ prior experiences, motivations, engagements, personhoods, and identities.…”
Section: Contemplating the Scholarshipmentioning
confidence: 99%
“…Their own efforts to transform the ways that students of color either view or express themselves in the world can, and most often do, perpetuate the very social injustices they are attempting to ameliorate due to an educator's own experience and expression of whiteness (T. L. Green & Dantley, 2013;Pennington, Brock, & Ndura, 2012). Because of these concerns, the critical lens must be turned inward and the praxis deepened if they, as white-identified individuals in the field of education, are to make any real contributions without extending the hand of racist, white-centric educational dominance Lazar & Offenberg, 2011;Manglitz, 2003). Crucial in this are the frameworks of critical pedagogy and its ability to liberate through education.…”
Section: Whiteness Racism and Educationmentioning
confidence: 99%
“…Self-driven education via social justice activism learning has made its mark in educational institutions through student grassroots efforts and the gathering of collectives dedicated to the engagement of a deconstructive discourse and social justice action (DeMatthews & Mawhinney, 2014;Smith & Lau, 2013). Critical pedagogies and theoretical frameworks concerning class, gender, and environmental justice, in addition to anti-racist curriculum, have been making their way slowly into the classrooms of middle schools, high schools, and universities (Boatright-Horowitz et al, 2012;Brown, 2004;Brunsma, Brown, & Placier, 2013;Chizhik & Chizhik, 2005;Dutta et al, 2016;Lazar & Offenberg, 2011;Nordstrom, 2015;Singer, 2016;Strmic-Pawl, 2015). Although many individuals learn about social and environmental justice issues through activism and formal educational institutions, social and environmental justice education-for white-identified individuals by white-identified individuals-is a relatively new phenomenon.…”
Section: Self-educating the "White-identified" Selfmentioning
confidence: 99%